Bahasa Inggris - Lavenia Horas; Syalwah; Nirmala Sari; Hilda Lisarib; Carolina Novi Mustikarini; Afrizal Firman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The beauty industry in Indonesia has grown notably over the past decade, driven by higher public awareness of self-care, evolving lifestyles, digital advances, and the country’s cultural diversity. This steady rise underscores the importance of having well-structured strategic planning to maintain sustainability and remain competitive in a constantly shifting market. This study examines how strategic planning is implemented within Indonesia’s beauty sector by identifying both internal and external factors that shape business strategies for local as well as multinational companies. It focuses on two central questions: (1) which major factors influence the development of Indonesia’s beauty industry, and (2) what types of strategic planning are used to support its expansion. The research employs a qualitative method based on secondary data. Porter’s Diamond Theory and a SWOT framework are used to explore the sources of competitiveness, while the TOWS matrix is applied to develop strategic alternatives. The results show that the industry’s progress relies not only on its internal strengths and limitations but also on how effectively it responds to external opportunities and potential risks. The study also highlights the need for cooperation among industry stakeholders, supportive government policies, and continuous innovation to keep pace with changing consumer preferences and increasing global competition.